Pengaruh Pemberian Sari Jahe Gajah (Zingiber officinale Rosc.) Pada Air Minum Terhadap Profil Darah Burung Puyuh (Coturnix coturnix Japonica) - Ahmad Sobingin; Rinawidiastuti Rinawidiastuti; Faruq Iskandar (Jurnal Riset Agribisnis dan Peternakan, 2019)
Ginger juice (Zingiber officinale Rosc.) In drinking water against erythrocytes, hemoglobin, and quail hematocrit (Cortunix cortunix Japonica). Research conducted at the Field Laboratory of Animal Husbandry Study Program, Faculty of Agriculture, Muhammadiyah University, Purworejo and Laboratory of Clinical Pathology Department, Faculty of Veterinary Medicine, Gajah Mada University. The study used was a 3-week-old quail (Cortunix cortunix Japonica) of 120 animals. The material used is a commercial amount of 7 sacks (350 kg), and 57.75 liters (70 kg ginger) ginger juice. The tools used are for quail the size of each box is 39 cm high, 50 cm long, and 40. cm wide, feed and drinking containers, digital scales, containers/cooler boxes, syringes, and EDTA tubes. The treatment given in this study was given ginger juice as follows; (0%), (5%), (10%), (15%), (20%) and (25%) ginger juice. The method used in this study is an experimental method using a Completely Randomized Design (CRD) consisting of 6 preparations and 4 replications and each repetition consists of 5 quails. The parameters seen were erythrocytes, hemoglobin, and hematocrit. Supplementation of ginger juice mixed in drinking water on erythrocytes was not significant (P> 0.05) in the amount of 1.53, 1.39, 1.15,1.38, 1, 48, and 1.14 million / mm3. Hemoglobin was significantly different (P <0.05) with levels of 10.29, 18.81, 13.05, 15.59, 10.91 and 11.13 g / dl. Hematocrit was not proven real (P> 0.05) with the percentage of 31.63, 32.00, 33.00, 34.63, 33.13, and 38.00%. Based on the results of the study it can be concluded that this study offers elephant ginger extract (Zingiber officinale Rosc.) At doses of 5 and 15% can increase blood hemoglobin levels of quails. Nevertheless, the results of the study gave the essence of stitching to provide coverage to the number of bird blood erythrocytes below the normal amount.